Whither globalisation and convergence? Asian examples and future research. Issue 1 (1st January 2017) - Rowley, Chris
Abstract: Among the most popular of buzzwords and debated topics for governments, policy-makers and management as well as academia are 'globalisation'. Under its influence, one implication is that there is 'convergence' around a set of universally applicable and transferable beliefs and 'global' standards or 'best' practices which in turn produce ever more standardization with homogenized and similar nations and practices – the 'McDonaldisation' of everything. However, this is not a new idea and needs historical grounding and context. Also, in Asia, we can see globalization differently with not only constraints and alternatives, but even counter trends at both institutional and cultural levels, such as post-1980s ideas of the 'Japanisation' of management and industries and now the so-called 'Korean Wave' of Korean entertainment and popular culture rolling out over parts of the world. This indicates that globalization's converging impacts are less all-powerful than is often portrayed and thought.